Letter from Lord Todd to Paul Bartlett - Todd, Alexander R. (Alexander Robertus) (1979)
Concerns Todd's receipt of the Lomonosov medal from the USSR Academy of Science as well as possible lecture topics for his upcoming trip to the United States.
Keywords: Akademii︠a︡ nauk SSSR; Bartlett, Paul D.; Todd, Alexander R. (Alexander Robertus), 1907-; Nobel Prize winners; DNA